Identity Matters: Teaching Transgender in the Women’s Studies Classroom - Drabinski, Kate (Radical Teacher, 2014)
Teaching transgender studies is often assumed to fall under the purview of gender and women’s studies programs and the GLBT studies programs often nested there where claims have been made on the territories of gender and sexuality. The questions that have long plagued these programs persist: Is our subject matter women and men, gays and lesbians, transgender people? Or is it rather the production of those categories and how they come to matter? What, exactly, is the object of our study, when that object is so often our own subjectivities and a necessarily moving target? Identities are historical artifacts rather than static realities, so to teach identity-based programs is to risk further calcifying the very categories that operate to oppress those of us who live on the margins of them. At the same time, those categories are necessary to our understanding of very real material histories of oppression and resistance; to teach as if identity is mere figment would render invisible the very real legacies of domination that must be understood if they are to be undone.